Managing Risk in the Pro-Empowerment Era of Mental Health Care: A Cross-Cultural Study of Social Work Perspectives in Hong Kong and Sydney. (22nd December 2020) - Cui, Jialiang; Mao, Limin; Newman, Christy E; Kwan, Chi Kin; Lancaster, Kari
Abstract: Risk management and empowerment have become key features of social work practice. Despite their increasing salience, relatively little is known about the perspectives of mental health social workers regarding how they navigate competing risk management approaches in modern practice that supports empowerment. The socio-cultural influences on risk management have also received insufficient attention in social work research. Focusing on these issues, this paper explored the perspectives of social workers in two geographically and culturally distinctive settings (i.e., Hong Kong and Sydney). Data were collected through semi-structured interviews with frontline social workers and were analysed using thematic analysis. Similar views were expressed by participants in both settings regarding assessment of clients' readiness for risk-taking. Differences were identified in their practices of negotiating the perspectives of other key stakeholders and can be attributed to the influences of distinctive cultural and socio-political contexts. These insights may contribute to the development of more systematic, localised and practice-based risk assessment guidelines for mental health practitioners working towards the empowerment of clients.